Can synaesthesia research inform cognitive science? - Cohen Kadosh, R; Henik, A (2007)
The renaissance of synaesthesia research has produced many insights regarding the aetiology and mechanisms that might underlie this intriguing phenomenon, which abnormally binds features between and within modalities. Synaesthesia is interesting in its own right, but whether it contributes to our knowledge of neurocognitive systems that underlie non-synaesthete experience is an open question. In this review, we show that results from the field of synaesthesia can constrain cognitive theories in numerical cognition, automaticity, crossmodal interaction and awareness. Therefore, research of synaesthesia provides a unique window into other domains of cognitive neuroscience. We conclude that the study of synaesthesia could advance our understanding of the normal and abnormal human brain and cognition.